SOLUSI PERMASALAHAN KOMPUTASI SKALA BESAR PADA SOFTWARE ADOBE FLASH DALAM PERANCANGAN MEDIA PEMBELAJARAN PENCARIAN EULERIAN CIRCUIT - Reza Wafdan; Mahyus Ihsan; Marwan Ramli; Hafnani Hafnani (Universitas Syiah Kuala, 2016)
Adobe Flash is a software that is used to build an interactive contents that can be attached in other things, such as presentations, games and e-learning. The Eulerian Circuit Search Instructional Media is one of examples in using Adobe Flash in building an interactive instructional media to solve graph theory problems. Visually, Adobe Flash is better than other programming software in general and it is the most suitable one for graph theory, as it uses graphics and visuals to solve problems. The weakness of Adobe Flash is when doing large scale calculations; such as when testing algorithms to find Eulerian circuits. Then an idea came about to complete the large scale calculations in Adobe Flash, which is commonly known as script time limit, with using other methodologies by changing script time limit on the settings, algorithms, partition the processes, and utulize the timers within the objects in the actionscript that handles the search algorithms of searching Eulerian circuit.